EFFECT OF SITAGLIPTIN ON GLYCEMIC CONTROL AND BEYOND - IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Ravichandar, Ramya; Nagarajan, Aravind Anapathoor (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to assess the pleiotropic effects of Sitagliptin as add-on therapy to the conventional antidiabetic drugs. Methods: This was designed as a prospective study. 140 patients with type 2 diabetes mellitus (T2DM) whose glycated hemoglobin (HbA1c) was >7% despite receiving education on diet and exercise and/or medications were enrolled in this study. Sitagliptin (100 mg) was administered once a day orally for 6 months as an add-on therapy with the conventional antidiabetic drugs. The outcome of the therapy was assessed on the level of improvement in the fasting plasma glucose, postprandial plasma glucose, HbA1c levels, lipid profile, body mass index, blood pressure, and albuminuria in the third and 6th month when compared to the first visit. Results: After 6 months of treatment with Sitagliptin, fasting blood glucose levels significantly reduced (202.6±49.21 to 186.1±50.14, p=0.029) as well as HbA1c (9.5±1.27 to 9.1±1.28, p=0.016). There was a statistically significant (p<0.001) reduction of blood pressure, cholesterol, and urinary albumin-creatinine ratio progressively. Conclusion: Sitagliptin has a significant effect on lipid profile, blood pressure and albuminuria in addition to its effect on blood glucose profile and HbA1c without many side effects, in patients with T2DM.